Effects of residual plastic film on crop yield and soil fertility in a dryland farming system - Dong WANG; Yue XI; Xiao-yan SHI; Chao-li GUO; Yu-jie ZHONG; Chao SONG; Yu GUAN; Lu HUANG; Qi-feng YANG; Feng-min LI (Journal of Integrative Agriculture, 2023)
Plastic film mulch in agricultural production becomes essential to maintaining crop yields in arid and semiarid areas. However, the presence of residual film in farmland soil has also drawn much attention. In this study, three experiments were conducted. The first two experimental designs included 0, 450, 1 350, and 2 700 kg ha−1 of residual film pieces of approximately 5 cm side length added to field soil (0–20 cm soil depth) for seven years and added to pots for four years. In the third experiment, 1 350 kg ha−1 of the residual film with different side lengths (2–5, 5–10, 10–15, and 15–20 cm) was added to field soil for six years to explore the effect of residual film fragment size on soil nutrients, soil microorganisms, crop growth and yields. The residual film had little effect on the soil moisture at a field depth of 0–2 (or 0–1.8) m. There were no significant effects on organic carbon, total nitrogen, inorganic nitrogen, total phosphorus or available phosphorus in the 0–20 cm soil layer. The presence of residual film decreased the richness and diversity of the bacterial community of the surface soil of the residual film, but it had no significant effect on the microbial community of the non-surface soil. The emergence rates of wheat and lentils occasionally decreased significantly with different amounts of residue fragments added to the field. At 450–2 700 kg ha−1, the residual film reduced the plant height and stem diameter of maize and significantly reduced the shoot biomass of harvested maize by 11–19%. The average yields of maize and potato over the seven years decreased, but there were almost no significant statistical differences among the treatments. These results provide important data for a comprehensive scientific understanding of the effects of residual film on soil and crops in dryland farming systems.